2010
DOI: 10.2105/ajph.2009.167064
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Ethnic Disparities in Patient Safety: A Qualitative Analysis

Abstract: Our findings suggest that organizational and health professional practices contribute to the higher risk of patient safety events. Descriptive epidemiological research is needed to explore the impact of the 3 patterns on patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
46
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 27 publications
0
46
0
7
Order By: Relevance
“…A previous qualitative study showed that actual shortfalls in quality of care for ethnic minority patients do occur and may lead to excess LOS and higher readmission rates among minority patients. For instance, language barriers between physician and patient may incur a higher risk of extra bed days or readmission because of a delayed or wrong diagnosis 25 , 26 , 28 , 44 . However, an appropriate reaction to language barriers may lead to appropriate extra LOS if for instance rehabilitation takes longer because of this.…”
Section: Discussionmentioning
confidence: 99%
“…A previous qualitative study showed that actual shortfalls in quality of care for ethnic minority patients do occur and may lead to excess LOS and higher readmission rates among minority patients. For instance, language barriers between physician and patient may incur a higher risk of extra bed days or readmission because of a delayed or wrong diagnosis 25 , 26 , 28 , 44 . However, an appropriate reaction to language barriers may lead to appropriate extra LOS if for instance rehabilitation takes longer because of this.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, patients who face language barriers are less likely than others to receive the same standard of medical care; are less likely to access preventative medicine and have an increased risk of non‐adherence to medication. Similarly, some studies indicated that language differences between physician and patient were associated with a higher risk of serious incidents 15,16 . Along this line, access to interpreters becomes a key factor in addressing language barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, we conducted a qualitative interview study with care providers, to better understand the process underlying ethnic differences in patient safety [14]. Three patterns of interactions between professional and patient that can contribute to ethnic differences in patient safety were identified: inappropriate responses by health care providers to objective characteristics of immigrant patients, such as low Dutch proficiency; misunderstandings between patients and care providers due to differences in illness perceptions and expectations about health care; and inappropriate care because of providers’ prejudices against or stereotypical ideas about patients of non-Dutch ethnic origin.…”
Section: Introductionmentioning
confidence: 99%
“…2) Healthcare characteristics (such as a protocolled use of interpreters): we also relied upon Stronks et al [15] along with the CLAS standards to define healthcare characteristics [16]. 3) Patient-care provider interaction: we used the work of Suurmond et al [14]. …”
Section: Introductionmentioning
confidence: 99%